A landscape analysis of nutrition initiatives in Madhya Pradesh: Policies, actors, and networks - Batra-Dua, Sunaina; Menon, Subhadra; Mathur, Shivani; Sharma, Gina; Chauhan, Kavita; Bose, Vijayluxmi (International Food Policy Research Institute, 2014)
The silent scourge of undernutrition and major nutritional deficiencies of public health importance persists across India despite decades of planned programmes and interventions. The maternal and child undernutrition scenario in India represents a complex set of determinants, including poverty, lack of knowledge, and access. Other factors that confound this dangerous interplay of barriers are erosion of conventional food consumption patterns exacerbated by poor hygienic practices, diseases such as malaria and diarrhoea, and lack of access to safe water and sanitation.